Incidence of aflatoxins and fumonisins in grain, masa and corn tortillas in four municipalities in the department of Lempira, Honduras. Issue 12 (December 2021) - Cabrera-Meraz, Jeimy; Maldonado, Luis; Bianchini, Andréia; Espinal, Raúl
Abstract: In Honduras, corn is the most important staple food for the majority of the population. This high-demand crop is susceptible to biological contamination with mycotoxins, which could represent a latent hazard for consumers. To assess the incidence of aflatoxins and fumonisins in grain, masa and tortilla, and the dietary exposure to these substances among consumers, a study was conducted in four municipalities in the department of Lempira. Total aflatoxin and fumonisin content were quantified by fluorometry in 144 samples from 48 farmers. Sixty five percent of the samples were contaminated with aflatoxins with levels of 1.28–32.05, 1.15 to 12.61, and 1.01–5.98 μg/kg in grain, masa and tortilla, respectively. Fumonisins were detected in 100% of the samples at levels between 0.82 and 28.04, 0.66 and 14.36, and 0.63 and 12.04 mg/kg in grain, masa and tortilla, respectively. The reduction in aflatoxin and fumonisin contamination after processing grains into tortillas was of 83% and 52%, respectively. The difference in aflatoxin and fumonisin concentration in the three products was significant (p < 0.05). With a per capita tortilla consumption of 490 g/day, dietary exposure was estimated between 0.003 and 0.073 μg/kg bw/day for aflatoxins and 6.16 and 151.98 μg/kg bw/day for fumonisins. Therefore, the risk of exposure to mycotoxins in the evaluated communities was considered high. Mixed effect models showed that postharvest grain management and the nixtamalization process affect the incidence of mycotoxins in corn-based products. Abstract : Contamination, Exposure risk, Mycotoxins, Nixtamalization, Postharvest management.